Pengaruh Kompetensi dan Motivasi Kerja Pegawai Terhadap Kualitas Pelayanan, Kepuasan Konsumen Serta Citra Organisasi Pada Balai Pelatihan Kesehatan Provinsi Kalimantan Selatan - Junaidi Junaidi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
Implementation of Otoda, demands increased competence and motivation of government officials, whether from central government employees or the smallest local government officials (kelurahan). Changes to these human resources, ultimately expected to affect the performance of officials, as well as consumer satisfaction so that the good name (corporate image) of governance in this case the local government also increased. If it goes according to expectations, will create consumer satisfaction (people who enjoy public service (government). Problem Formulation: Is there a significant influence between employee competence and motivation on Service quality, customer satisfaction and organization image in Health Training Center of South Kalimantan Province. This type of research is explanatory research, ie this study will be examined the relationship or causal influence between variables through testing the hypothesis set previously. According to Neuman (1999: 22) Explanatory Research departs from the state of a phenomenon known and described, but it is necessary to do more in-depth study. Why the phenomenon occurs and how the phenomenon occurs. The study population is employees in the scope of the Health Service that utilizes the Training of Bapelkes of South Kalimantan province during 2010 until 2014.